Organizational Cronyism as an Antecedent of Ingratiation: Mediating Role of Relational Psychological Contract - Shaheen, Sadia; Bari, Muhammad Waseem; Hameed, Filza; Anwar, Muhammad Mudassar (Frontiers in Psychology, 2019)
The present study investigates the relatively less explored construct organizational cronyism as an antecedent of employees’ ingratiation. Moreover, the role of the relational psychological contract as a mediator between organizational cronyism and ingratiation is also examined. The data are collected from the employees working in different ministerial offices such as the ministry of defense production, human rights, parliamentary affairs, petroleum, and natural resources at Islamabad, Pakistan. Through convenience sampling approach, 250 employees provided data for this study. Due to sensitivity and less approachability to these organizations, the convenience sampling technique is used. The data are collected in two waves with twelve weeks interval. The results confirm that organizational cronyism is significantly related to the relational psychological contract which in turn result in employees’ ingratiation. The employees who have close ties with their leaders and enjoy extraordinary favors from their leaders, display more compliance behavior as compared to those employees who have distance from their leaders.